1990
DOI: 10.1113/jphysiol.1990.sp018346
|View full text |Cite
|
Sign up to set email alerts
|

Is increased metabolism in rats in the cold mediated by the thyroid?

Abstract: 1. In the rat variation of metabolic heat production is the principal effector of thermoregulation. There is a continuous relationship between ambient temperature and metabolic rat over the whole range of tolerable environmental temperature. The mechanism that controls metabolic rate is unknown; this paper reports an attempt to test whether thyroid hormones provide the controlling pathway. 2. First, the changes in metabolic rate and in the plasma concentrations of thyroid stimulating hormone (TSH), triiodothyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
2
3
0
Order By: Relevance
“…In the literature, reported values for the resting metabolism of euthyroid rats vary over a considerable range, namely between 1 2 and 2 1 (1 02) kg-' h-' (Nagasaka, Hirata, Sugano & Shibata, 1979;Liverini, Iossa & Barletta, 1994). The values obtained in our experiments are the same as the means reported by the latter group and close to those in other reports (Buser, Kopp, Gehr, Weibel & Hoppeler, 1982;Whitaker, Hussain, Hervey, Tobin & Rayfield, 1990;Himms-Hagen et al 1994).…”
Section: Hormone Concentrationssupporting
confidence: 90%
See 1 more Smart Citation
“…In the literature, reported values for the resting metabolism of euthyroid rats vary over a considerable range, namely between 1 2 and 2 1 (1 02) kg-' h-' (Nagasaka, Hirata, Sugano & Shibata, 1979;Liverini, Iossa & Barletta, 1994). The values obtained in our experiments are the same as the means reported by the latter group and close to those in other reports (Buser, Kopp, Gehr, Weibel & Hoppeler, 1982;Whitaker, Hussain, Hervey, Tobin & Rayfield, 1990;Himms-Hagen et al 1994).…”
Section: Hormone Concentrationssupporting
confidence: 90%
“…The values obtained in our experiments are the same as the means reported by the latter group and close to those in other reports (Buser, Kopp, Gehr, Weibel & Hoppeler, 1982; Whitaker, Hussain, Hervey, Tobin & Rayfield, 1990;Himms-Hagen et al 1994). …”
Section: Hormone Concentrationssupporting
confidence: 81%
“…Many studies have reported that thyroid function in humans adapts to environmental conditions such as ambient temperature, photoperiod, and season, but the results have not been consistent because more than one parameter may mediate thyroid function [2][3][4]10]. Although similar findings were reported in rat [11,13], sheep [15], and dog [12], the only hormones measured were serum total thyroxine (tT 4 ), triiodothyronine (tT 3 ), and TSH. There has been only one report about seasonal changes in thyroid function in the dog [12], but the details of such changes have remained unclear because only tT 4 and tT 3 levels were measured.…”
mentioning
confidence: 98%
“…tT 4 post TSH level in November is also significantly higher than in Dec. 17.0 17.1 Exposure to cold in January might create a condition like Cushing's syndrome because of stress, although the cortisol level was not measured in the present study. Many reports about the influence of environmental temperature--specifically, exposure to cold--on the thyroid hormones of the human being [2,7] and rat [11,13] suggest that cold exposure activates pituitary and thyroid functions and increases the basal metabolic rate. In our present study, the response to the TSH-stimulating test was increased in August and November.…”
mentioning
confidence: 99%
“…Most small mammals respond to cold exposure by augmenting thyroid-mediated processes (9,17). These increase basal metabolism and heat production (45,48). Poikilotherms on the other hand, generally show a decrease in both thyroid activity and metabolism in the cold (5,12).…”
mentioning
confidence: 99%